DETERMINASI KEPEMILIKAN MANAJERIAL, DIVIDEN, PROFITABILITAS DAN FREE CASH FLOW TERHADAP KEBIJAKAN UTANG PADA PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI BARANG KONSUMSI - Fifi Alfinna Damayanti; Wahyu Dwi Warsitasari (Bajang Institute, 2022)
This study aims to see the effect of managerial ownership, dividends, profitability and free cash flow on debt policy in manufacturing companies listed on the BEI in the consumer goods industry sector for the period 2017-2021. This research takes quantitative techniques and is a type of associative research. The population is 10 manufacturing companies that have been listed on the BEI for the consumer goods industry sector for the 2017-2021 period, which can be accessed at www.idx.co.id. The data analysis technique used in this research is descriptive statistics and panel data regression analysis using the Eviews12 program. Based on the results of research conducted with panel data regression analysis in the above study which explains managerial ownership, dividends, profitability and free cash flow on debt policy, it can be concluded that the results of the test show managerial ownership, dividends, free cash flow have a positive effect on the debt policy of manufacturing companies listed on the Indonesia Stock Exchange for the Consumption Sector, while profitability has no negative effect on the debt policies of manufacturing companies listed on the Indonesia Stock Exchange for the Consumption Sector